Consider the boundary value problem(BVP) defined by laplaces equation.
uxx+uyy=0 on the square o<x,y<2
subjected to the boundary conditions:
u(0,y)=0 ,u(x,2)=0 ,u(2,y)=0 ,u(x,0)=100sin(πx/2)
Solve the BVP using method of separation of variable.
The given equation is -
"\\dfrac{\\partial^{2}u}{\\partial x^{2}}" "+\\dfrac{\\partial^{2}u}{\\partial y^{2}}=0.........................................1)"
Let "u=XY.............................................2)"
where "X" is a function of "x" and "Y" is a function of "y" , only then ,
"\\dfrac{\\partial^{2}u}{\\partial x^{2}}=\\dfrac{\\partial^{2}(XY)}{\\partial x^{2}}=Y\\dfrac{d^{2}X}{dx^{2}}" and
"\\dfrac{\\partial^{2}u}{\\partial y^{2}}=\\dfrac{\\partial^{2}(XY)}{\\partial y^{2}}=X\\dfrac{d^{2}Y}{dy^{2}}"
"\\therefore" From (1), "YX^{''}+XY^{''}=0"
"\\implies" "\\dfrac{X^{''}}{X}+\\dfrac{Y^{''}}{Y}=0"
Now , we will make some cases -
Case I. When "\\dfrac{X^{''}}{X}=-\\dfrac{Y^{''}}{Y}" "=p^{2}(say)"
"i) \\ \\dfrac{X^{''}}{X}=p^{2}"
"X^{''}-P^{2}X=0"
Auxiliary equation is-
"m^{2}-p^{2}=0"
"m={\\pm}p"
"\\therefore" "CF=c_1e^{px}+c_2e^{-px}"
"PI=0"
"\\therefore" "X=" "c_1e^{px}+c_2e^{-px}"
"ii)" "\\ \\dfrac{Y^{''}}{Y}=p^{2}\\implies" "Y^{''}+P^{2}Y=0"
Auxiliary equation is "-"
"m^{2}+p^{2}=0\\implies" "m={\\pm}pi"
"\\therefore" "CF=c_3cospy+c_4sinpy"
"PI=0"
"\\therefore" "y=c_3cospy+c_4sinpy"
Now , we have given some boundary conditions making use of them now -
"X(0)=0"
"\\implies" "c_{1}+c_{2}=0" "\\implies c_2=-c_1"
"X(x)=0"
"\\implies" "c_{1}e^{px}+c_2e^{-px}=0" "\\implies" "c_1(e^{px}+e^{-px})=0"
"\\implies" "c_1=0" (Since "e^{px}-e^{-px}" "\\neq0(as\\ p\\neq0\\neq l)"
"\\therefore" "c_2=0"
"\\therefore" "X=0\\implies" "u=XY=0" which is impossible .
Hence Case 1 is rejected .
"Case \\ 2)" when "\\dfrac{X^{''}}{X}=-\\dfrac{Y^{''}}{Y}=0"
"i)" "\\dfrac{X^{''}}{X}=0"
"\\implies" "X^{''}=0\\implies" "X=c_5x+c_6"
"ii)" "-\\dfrac{Y^{''}}{Y}=0"
"\\implies" "Y^{''}=0\\implies" "Y=c_7y+c_8"
Now , "X(0)=0\\implies" "c_6" "=" 0
"X(x)=0"
"\\implies" "c_5+c_6=0\\implies""c_5l=0"
"\\implies" "c_5=0"
"\\therefore X=0"
"\\therefore u=XY=0" which is impossible .
Hence we reject case 2 also .
"Case \\ 3)" when
"\\dfrac{X^{''}}{X}=-\\dfrac{Y^{''}}{Y}=-p^{2}(say)"
"(i)" "\\dfrac{X^{''}}{X}=-p^{2}" "\\implies \\dfrac {d^{2}X}{dx^{2}}+p^{2}=0"
"\\implies" "X^{''}+p^{2}X=0"
Auxiliary equation is given by -
"=m^{2}+p^{2}=0\\implies" "m={\\pm}pi"
"CF=c_9cospx+c_{10}sinpx"
"PI=0"
"X=c_9cospx+c_{10}sinpx"
"(ii)" "-\\dfrac{Y^{''}}{Y}=-p^{2}" "\\implies \\dfrac{d^{2}y}{dy^{2}}-p^{2}y=0"
Auxiliary equation is -
"m^{2}-p^{2}=0"
"m={\\pm}p"
"\\therefore CF=c_{11}e^{py}+c_{12}e^{-py}"
"PI=0"
hence , "Y=c_{11}e^{py}+c_{12}e^{-py}"
Now , "X(0)=0 \\implies c_{9}=0"
"\\therefore X=c_{10}sinpx"
"X(l)=0"
"=c_{10}sinpl=0"
"\\therefore sinpl=0=sinn{\\pi}, n\\in I"
"\\therefore" "p=\\dfrac{n{\\pi}}l"
"\\therefore" "X=c_{10}sin\\dfrac{n{\\pi}x}{l}" .............................................................3)
Again "Y(0)=0"
"\\therefore c_{11}+c_{12}=0 \\therefore c_{11}=-c_{12}"
"Y=c_{11}(e^{py}-e^{-py})=c_{11}(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})"
"\\therefore u=XY=c_{10}c_{11}sin\\dfrac{n{\\pi}x}{l}[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]"
or "u(x,y)=b_nsin\\dfrac{n{\\pi}x}{l}[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]"
Now "u(x,0)=100sin\\dfrac{{\\pi}x}{2}=b_nsin\\dfrac{n{\\pi}x}{l}[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]"
"=b_{n}=\\dfrac{100sin\\dfrac{{\\pi}x}{2}}{sin\\dfrac{n{\\pi}x}{l}[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]}"
"u(x,y)=" "[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]\\dfrac{100sin\\dfrac{{\\pi}x}{2}}{sin\\dfrac{n{\\pi}x}{l}[(e^\\dfrac{n{\\pi}}{l}-e^\\dfrac{-n{\\pi}}{l})]}" "sin\\dfrac{n{\\pi}x}{l}"
"u(x,y)=100sin\\dfrac{{\\pi}x}{2}"
which is given solution .
Comments
Leave a comment